Switching pattern of healthcare services and its determinants among patients with communicable and non-communicable diseases in India - Ajit Kumar Jaiswal; Manoj Alagarajan; Mrinmoy Pratim Bharadwaz; Shoummo Sen Gupta; Pravin Kumar Singh (Elsevier, 2024)
Background: The current study investigates the switching behaviour and patterns among patients in India, particularly in the context of various ailments such as Non-Communicable Diseases (NCDs), Communicable Diseases (CDs), and other health issues. To evaluate people's behaviour towards accessing healthcare facilities in public and private healthcare providers separately for CDs, NCDs, and other ailments. Material and methods: The study design is observational and cross-sectional. The study included data from NSS 71st, NSS 75th, and LASI wave-1 datasets, which provide information on the incidence of switching behaviour among patients with different types of ailments. Statistical analysis used: The Binary logistic regression analysis has been used to examine the determinants of switching behaviour in usage of healthcare facilities. Prevalence estimates were exhibited using weighted % and 95 % confidence intervals (CI). P values < 0.05 were considered statistically significant. Results: Present study revealed that patients' behaviour in accessing healthcare facilities is influenced by a multitude of factors, including the nature of their ailment, socio-economic status, education, and regional disparities. Notably, patients suffering from NCDs exhibit a higher propensity for switching between public and private healthcare services, with a preference for the latter. The study found that among patients who were paying for special types of wards, there were significantly lower odds of switching behaviour. Conclusions: The research highlights the nuanced dynamics of healthcare service utilization in India and underscores the need for tailored strategies to address the specific challenges posed by NCDs and communicable diseases while ensuring equitable and accessible healthcare services for all.